Praktik Digitalisasi Koleksi Perpustakaan Perguruan Tinggi di Indonesia Tahun 2017 s.d. 2022 - Saputra, Andi; Desriyeni, Desriyeni (Media Pustakawan, 2024)
Digitalization is one of the methods carried out to develop library collections. This study aims to evaluate the digitization practices carried out in university libraries in Indonesia by understanding the types of collections and the purpose of implementing digitization projects, the procedures and stages of digitalization that are carried out, as well as the obstacles found in carrying out digitalization projects. The data were evaluated qualitatively in the form of a literature study. The data source comes from the results of previous research on digitization projects in ten domestic university libraries, which were carried out in the period from 2017 to 2022. The results found that the gray literature collection (student final project) is the most widely transferred type of collection besides the book collection. The main goal is to improve access and dissemination of information. Meanwhile, the process and stages of digitization that are passed are not much different between university libraries that are used as research samples. The difference lies in the handling of collections after the digitization process is completed, which includes storage, access management, and preservation. Several challenges are faced in the digitalization process, such as budget limitations, lack of facilities and infrastructure, and limited staff abilities and knowledge about digitalization. The conclusion is that most universities are weak in planning and do not have a clear policy for carrying out digitalization projects, which is the cause of various obstacles during the digitalization project.